PENTINGNYA MENENTUKAN PASAR SASARAN SEBELUM MENJUAL PRODUK BAGI USAHA KECIL MENENGAH (UKM) DI KELURAHAN BULUSAN KECAMATAN TEMBALANG KOTA SEMARANG - Kuswardani, DC.; Widayat, Guruh Mulia; Mara, Lusa (Jurnal Abdimas Bina Bangsa, 2025)
This Community Service Activity aims to improve the understanding and ability of Small and Medium Enterprises (SMEs) in Bulusan Village, Tembalang District, Semarang City, in determining the right target market before selling products. Determining the target market is a very important strategic step for SMEs to ensure that their products can be accepted and compete in the appropriate market. However, many SMEs still face difficulties in understanding relevant market characteristics and effective segmentation strategies. The method used in this activity is through socialization, with the material provided including an introduction to the concept of segmentation, targeting, and positioning (STP), consumer needs analysis, and determining the target market using a simple and applicable approach. The results of the activity show that SMEs who participate in this program have a better understanding of the importance of the target market, are able to identify potential market segments, and begin to implement more targeted marketing strategies. The impact is an increase in the effectiveness of product marketing and the potential for increasing the competitiveness of their businesses in the local market. This activity is expected to provide a real contribution in supporting the development of SMEs in the Bulusan area, Tembalang District, Semarang City